2022
DOI: 10.1002/14651858.cd013525.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pain management for medical abortion before 14 weeks’ gestation

Abstract: Pain management for medical abortion before 14 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…There is no consensus within the literature on analgesia for those who experience pain during medical abortion although a Cochrane Review is currently in progress on this topic. 74 There is currently significant variation in practice described in terms of the analgesics offered, the schedule and route of administration and whether these are provided by health services.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus within the literature on analgesia for those who experience pain during medical abortion although a Cochrane Review is currently in progress on this topic. 74 There is currently significant variation in practice described in terms of the analgesics offered, the schedule and route of administration and whether these are provided by health services.…”
Section: Discussionmentioning
confidence: 99%
“…We contacted experts and organizations in the field to obtain additional information on relevant studies, including those that are ongoing. We searched numerous grey literature sites, which are detailed in the full Cochrane Review publication [10]. We also searched clinicaltrials.gov and www.who.int/trialsearch to look for ongoing studies.…”
Section: Methodsmentioning
confidence: 99%
“…This adverse effect is important especially if someone is managing the process at home. The Cochrane review on pain management for first‐trimester medical abortion provides some information for health care providers and patients 4 . This review identified only 4 RCTs and a single nonrandomized intervention study.…”
Section: Practice Evidence For Medical First‐trimester Abortionsmentioning
confidence: 99%
“…Currently, medical abortion accounts for more than half of the abortions in the United States, 2 and the recent court ruling may increase that percentage. Two new Cochrane systematic reviews summarize the data to date on different medical methods for first‐trimester abortion 3 and related pain management 4 …”
Section: Practice Evidence For Medical First‐trimester Abortionsmentioning
confidence: 99%
See 1 more Smart Citation